Elucidating the interaction mechanism of eriocitrin with β-casein by multi-spectroscopic and molecular simulation methods. (September 2019) - Cao, Xiangyu; He, Yonglin; Kong, Yuchi; Mei, Xueying; Huo, Yapeng; He, Yin; Liu, Jianli
Abstract: Eriocitrin is a flavanone glycoside which exists in lemon or lime citrus fruits. It exhibits antioxidant, anti-cancer and anti-allergy activities. β-casein is important protein in bovine milk, under appropriate conditions, it can form stable micelle like structures in aqueous solution, which is beneficial to the nutritional ingredient transportation in body. In this work, the interaction mechanisms of eriocitrin with β-casein under physiological conditions (pH = 7.4) were investigated by utilizing multi-spectroscopic techniques and molecular docking methods. The endogenous fluorescence of β-casein was quenched by the interaction with eriocitrin and the quenching mode was static quenching. The interaction of eriocitrin with β-casein was a spontaneous reaction principally driven by hydrophobic interaction. At 310 K, the binding constant was equal to 6.68 × 10 5 L mol −1 and the number of binding sites was approximately equal to 1. The changes of β-casein conformation were confirmed by FTIR, circular dichroism spectroscopy and synchronous fluorescence spectroscopy. Moreover, molecular docking studies illustrated the most possible binding position of eriocitrin on β-casein. Graphical abstract: The binding interaction of eriocitrin with β-casein nanoparticles under physiological conditions (pH = 7.4) was studied by multi-spectroscopic and molecular docking methods.Image 1 Highlights: Eriocitrin binds to the hydrophobic core of β-casein. Hydrophobic interaction are predominating in binding process. β-casein might act as a as transporter for the delivery of eriocitrin.